A method to predict the ultimate tensile strength of 3D printing polylactic acid (PLA) materials with different printing orientations. (15th April 2019) - Yao, Tianyun; Deng, Zichen; Zhang, Kai; Li, Shiman
Abstract: 3D Printing is widely used in scientific researches and engineering applications, ranging from aerospace to biomedicine. However little is known about the mechanical properties of 3D printing materials. In order to promote the mechanical analysis and design of 3D printing structures, the ultimate tensile strength of FDM PLA materials with different printing angles were studied theoretically and experimentally. A theoretical model was firstly established to predict the ultimate tensile strength of FDM PLA materials based on transverse isotropic hypothesis, classical lamination theory and Hill-Tsai anisotropic yield criterion, and then verified by tensile experiments. Compared with previous models, this model provided two kinds of in-plane shear modulus calculation methods, so the calculation results were more reliable. The specimens, designed according to the current plastic-multipurpose test specimens standard ISO 527-2-2012, were printed in seven different angles ( 0 ∘, 15 ∘, 30 ∘, 45 ∘, 60 ∘, 75 ∘, 90 ∘ ) with three layer thicknesses (0.1 mm, 0.2 mm, 0.3 mm) for each angle. The relative residual sum of squares between theoretical data and experimental data were all close to zero, so the results that the theoretical model can accurately predict the ultimate tensile strength of FDM materials for all angles and thicknesses were confirmed. It was also found that the ultimate tensile strength decreased as the printing angle becomes smaller or the layer becomes thicker. This theoretical model and experimental method can also be applied to other 3D printing materials fabricated by FDM or SLA techniques.